Efeito protetor in vivo de vacinas de células dendríticas sensibilizadas com RNA de células MC-38 pré-tratadas com agentes antineoplásticos em concentrações efetivas minímas - Camargo, Marcela Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
We have recently observed that treatment of colon tumor cells with low concentration of paclitaxel increased the expression of several genes associated with antigen-presenting machinery. Since 5-fluoruracil (5-FU) is the main antineoplastic agent for colon cancer, in this study we aimed to evaluate immunomodulatory properties analyzing: a) if the DC transfection with drug-treated tumor cells RNA, enhances the effectiveness of DC-based vaccine; b) if the modulatory effects of vaccine can be observed in vivo, and c) if the combination of DC with low dose chemotherapy schedule improves the antitumor responsiveness. To achieve these goals s.c. MC-38 bearing C57/Bl-6 mice were treated with DC sensitized with RNA from tumor cells pre-treated with the minimum effective concentration (MEC) of 5-fluorouracil. Our results of studies show that vaccination with tumor RNA-transfected DC delays the tumor growth, increases the percentage of CD86+ (35%) CD40+ (63%) and MHC class II+ (47%) DC and significantly increases the in vitro production of IFN-ɣ. These results suggest that treatment of tumor cells with 5-FU induces transcriptional changes that can be transfered to DC by RNA transfection, enhancing their ability to stimulate the antitumor response
Keywords: Cólon Câncer; Reto Câncer; Agentes antineoplasicos; Células dendríticas; Quimioterapia; Vacinas; Dendritic cells